2023
DOI: 10.3390/jpm13020319
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Frailty Syndrome in Men with Metastatic Prostate Cancer: A Scoping Review

Abstract: Most patients with metastatic prostate cancer (mPCa) are older. In addition, current geriatric oncology guidelines suggest that all cancer patients aged over 70 years should undergo a comprehensive geriatric assessment (CGA), with the identification of frailty syndrome being crucial for clinical decisions. Frailty can be associated with lower quality of life (QoL) and interfere with the feasibility or side effects of oncology treatments. Methods: We performed a systematic literature search to evaluate frailty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Few studies have compared the level of frailty between patients with metastatic vs. localized PCa [41][42][43][44][45][46][47]. A recent review analyzed frailty syndrome in patients with mPCa [27], showing a prevalence between 30-70% depending on the geriatric assessment tool used. Frailty was also identified as associated with other CGA assessments and quality of life assessment results, with mCaP patients being frailer and showing poorer HRQoL compared to those without metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have compared the level of frailty between patients with metastatic vs. localized PCa [41][42][43][44][45][46][47]. A recent review analyzed frailty syndrome in patients with mPCa [27], showing a prevalence between 30-70% depending on the geriatric assessment tool used. Frailty was also identified as associated with other CGA assessments and quality of life assessment results, with mCaP patients being frailer and showing poorer HRQoL compared to those without metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies to date have demonstrated differences in frailty syndrome between patients with mPCa and localized prostate cancer. A scoping review which analyzed the prevalence of frailty syndrome in mPCa found that 70% of patients with mPCa were frailer than localized patients [27]. We also propose to evaluate the role of other geriatric variables such as depressive symptoms and insomnia, given that studies have linked androgen depletion to depressive symptoms and/or insomnia in men without prostate cancer [28][29][30][31] and in patients with prostate cancer [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse cardiovascular, metabolic, cognitive and musculoskeletal effects of exposure to androgen deprivation therapy (ADT) also lead to an increase in the number of accidental falls and fractures (Feng et al, 2018). In addition, since the incidence of prostate cancer is significantly related to age, older patients have other comorbidities that can significantly affect their physical function, generally placing the body at greater risk of frailty (Mafla‐España et al, 2023). Therefore, lifestyle modification measures (such as diet modification and physical activity) are recommended to reduce adverse reactions and improve quality of life in men with prostate cancer (Chan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%